Electron beam fuse wire additive manufacturing method of gradient TA15 titanium alloy
Through the electron beam fuse additive manufacturing method of gradient TA15 titanium alloy, the problem of difficulty in processing complex structure TA15 titanium alloy parts in traditional manufacturing processes is solved, and the preparation of TA15 alloy with high density and excellent mechanical properties is achieved, which is suitable for the manufacturing of high-performance titanium alloy parts in the aerospace field.
Patent Information
- Application Number
- CN202411713431.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional manufacturing processes are difficult to meet the processing and manufacturing needs of TA15 titanium alloy parts in complex structures, which leads to difficult processing and poor surface quality, hindering the promotion and popularization of high-performance titanium alloy parts in the aerospace field.
An electron beam fuse additive manufacturing method using gradient TA15 titanium alloy is used to pre-treat the printing wire and additive substrate, set up a printing program, use electron beams as heat source for printing, and adjust the process parameters to obtain a TA15 alloy with good forming, dense tissue and gradient effect.
The rapid and direct formation of complex TA15 titanium alloy members was achieved, and a gradient TA15 alloy with high density, no cavity and cracks was obtained, showing excellent mechanical properties, including high tensile yield strength and elongation, solving the difficulties in the preparation of large-sized TA15 alloy members.
Smart Images

Figure CN119525678A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additive manufacturing, and in particular relates to an electron beam fuse additive manufacturing method for a gradient TA15 titanium alloy. Background Art
[0002] TA15 titanium alloy belongs to the near-α-type titanium alloy. The alloy is mainly strengthened by solid solution through the α-stabilizing element Al. At the same time, the neutral element Zr and the β-stabilizing elements Mo and V are added to reduce the phase transition temperature to improve the process performance. Therefore, it has both the good thermal strength and weldability of α-type titanium alloy and the process plasticity close to α+β-type titanium alloy. Compared with Ti6Al4V, it has higher room temperature and high temperature strength, fracture toughness, fatigue limit, stress resistance, corrosion resistance and welding performance. The working time at a working temperature of 500°C can reach 3000h. With its excellent performance, TA15 titanium alloy is suitable for the preparation of aircraft, aero engines and new generation tactical aircraft used at 500°C. The welding structural parts and load-bearing structural parts of missiles, cruise missiles, launch vehicles and satellites, such as casings and high-speed aircraft wings, are mainly processed by casting, forging and machining. However, the high activity, low thermal conductivity and high deformation resistance of TA15 alloy make its processing and manufacturing extremely difficult. The tool wear is serious during machining and the surface quality is poor. It is a difficult-to-process material recognized by the industry. With the increasing complexity, lightweight and structural integration of parts design in the aerospace field, traditional manufacturing processes are increasingly unable to meet the processing and manufacturing needs of complex structure TA15 parts, which seriously hinders the promotion and popularization of high-performance titanium alloy parts in the aerospace field. Summary of the invention
[0003] In view of this, the present invention aims to propose an electron beam fuse additive manufacturing method for gradient TA15 titanium alloy to solve the problem that traditional manufacturing processes are increasingly unable to meet the processing and manufacturing needs of complex structure TA15 parts.
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] An electron beam fuse additive manufacturing method for gradient TA15 titanium alloy, comprising the following steps:
[0006] Step 1: Pre-treat the printing filament and additive substrate;
[0007] Step 2: Set up the printing program, build a 3D solid model based on the target TA15 titanium alloy, import the slices, set the scanning path, preheating parameters and printing process parameters;
[0008] Step 3: Turn on the equipment and evacuate to 9.9×10-3Pa. Print TA15 alloy according to the set printing parameters and procedures to complete all layers.
[0009] Furthermore, in step 1, the additive substrate is a TA1 substrate with a substrate size of 200 mm×10 mm×10 mm, and the printing wire is a TA15 alloy wire with a wire diameter of 1.6 mm.
[0010] Furthermore, the preprocessing in step 1 includes the following steps:
[0011] S1: Soak the TA15 alloy wire in acetone for cleaning;
[0012] S2: Place the TA15 alloy wire in a drying oven and dry it at a constant temperature of 60°C for 4 hours;
[0013] S3: Use an angle grinder to grind the surface of the TA1 substrate until it is smooth;
[0014] S4: Wipe the surface of the TA1 substrate with acetone and alcohol, and then soak and clean it with acetone;
[0015] S5: Place the TA1 substrate in a drying oven and dry it at a constant temperature of 60° C. for 4 hours.
[0016] Furthermore, the composition of the TA15 alloy wire is: Al 6.58wt.%, V 2.3wt.%, Zr 1.94%wt.%, Mo.1.42wt.%, Si≤0.05wt.%, Fe≤0.05wt.%, O≤0.1wt.%, N≤0.01wt.%, C≤0.01wt.%, H≤0.01wt.%, and the rest are Ti elements and unavoidable impurity elements.
[0017] Furthermore, the TA1 substrate contains 99.9wt.% Ti element and other avoidable impurity elements.
[0018] Furthermore, the angle between the wire feed nozzle of the printing wire and the TA1 substrate is controlled at 40°.
[0019] Furthermore, the length from the wire feeding nozzle of the printing wire to the central axis of the electron beam is 5-15 mm.
[0020] Furthermore, the preheating parameters in step 2 are: acceleration voltage of 60 kV, focusing current of 1030 mA, beam density of 25 mA, and preheating printing speed of 500 mm / min.
[0021] Furthermore, the printing process parameters in step 2 are: acceleration voltage of 60 kV, focusing current of 1030 mA, beam density of 25-30 mA, printing speed of 800 mm / min, wire feeding speed of 1-1.4 m / min, knob control speed coefficient of 80%, and interlayer cooling time of 5 s.
[0022] Furthermore, the scanning path in step 2 is a unidirectional linear motion path.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The method for preparing gradient TA15 titanium alloy components provided by the present invention uses wire as printing material, has low material cost and high deposition efficiency, can quickly and directly form complex TA15 titanium alloy components, and by adjusting process parameters, can obtain a well-formed, densely organized TA15 alloy with a gradient effect.
[0025] 2. The gradient TA15 alloy additive manufacturing method of the present invention uses an electron beam as a heat source for melting the printing wire; electron beam technology has the advantages of high power, high energy utilization, adaptability to vacuum processing environment and high deposition efficiency, and can effectively prevent the generation of oxides during the printing process and affect material properties; the use of electron beams for additive manufacturing can achieve near-net rapid forming and high-quality forming of large and complex metal components, can achieve integrated preparation of form and properties, and effectively solve the problem of preparing large-size TA15 alloy components.
[0026] 3. The gradient TA15 alloy component prepared by the present invention has high density and no obvious defects such as voids and cracks, and the density is as high as 99.99%.
[0027] 4. The present invention adopts electron beam fuse additive manufacturing, and the gradient TA15 alloy obtained by deposition exhibits excellent mechanical properties. Its tensile yield strength reaches 915MPa, and its elongation is as high as 12%. At the same time, a smooth transition can be achieved between the deposited TA15 alloy and the substrate interface without cracks or warping, avoiding the high cost of using substrates with the same composition and the problem of being unable to produce in large quantities.
[0028] 5. The gradient TA15 alloy additive manufacturing method provided by the present invention is scalable and is also suitable for the rapid preparation of high-melting-point and high-activity alloys and the near-net forming of complex components. It can realize the rapid preparation of complex configurations with integrated structure and performance and has strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0030] Figure 1 A gradient TA15 titanium alloy component prepared by electron beam fused additive manufacturing;
[0031] Figure 2 Gradient TA15 titanium alloy component 2 prepared by electron beam fused additive manufacturing;
[0032] Figure 3 Gradient TA15 titanium alloy component three prepared by electron beam fused additive manufacturing;
[0033] Figure 4 Phase spectra of the obtained gradient TA15 alloy in different regions;
[0034] Figure 5 To obtain the microstructure and α phase thickness distribution of the gradient TA15 alloy in different regions in the deposition direction;
[0035] Figure 6 The tensile stress-elongation curves of different regions of the gradient TA15 alloy as deposited are obtained. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely explain the technical solutions in the embodiments of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict, and the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0037] Specific implementation method 1: See Figure 1-6 The present embodiment describes an electron beam fused additive manufacturing method for a gradient TA15 titanium alloy, which comprises the following steps:
[0038] Step 1: Pre-treat the printing filament and additive substrate;
[0039] Step 2: Set up the printing program, build a 3D solid model based on the target TA15 titanium alloy, import the slices, set the scanning path, preheating parameters and printing process parameters;
[0040] Step 3: Turn on the equipment and evacuate to 9.9×10-3Pa. Print TA15 alloy according to the set printing parameters and procedures to complete all layers.
[0041] In step 1, the additive substrate is a TA1 substrate with a substrate size of 200 mm × 10 mm × 10 mm, the printing wire is a TA15 alloy wire with a wire diameter of 1.6 mm, and the pretreatment in step 1 includes the following steps:
[0042] S1: Soak the TA15 alloy wire in acetone for cleaning;
[0043] S2: Place the TA15 alloy wire in a drying oven and dry it at a constant temperature of 60°C for 4 hours;
[0044] S3: Use an angle grinder to grind the surface of the TA1 substrate until it is smooth;
[0045] S4: Wipe the surface of the TA1 substrate with acetone and alcohol, and then soak and clean it with acetone;
[0046] S5: Place the TA1 substrate in a drying oven and dry it at a constant temperature of 60° C. for 4 hours.
[0047] The TA15 alloy wire with a diameter of 1.6 mm was pickled to remove the surface oxide film, and then soaked and cleaned with acetone to ensure that there was no oil impurities on the surface of the TA15 alloy wire. The surface of the TA1 pure titanium substrate with a size of 200 mm × 1 00 mm × 10 mm was polished with an angle grinder until the surface was smooth and clean, and then the surface was wiped with acetone to remove the oil impurities on the surface of the substrate. The TA15 alloy wire and the TA1 substrate were placed in a drying oven and dried at a constant temperature of 60 ° C for 4 hours to remove the moisture in the TA15 alloy wire and the TA1 pure titanium substrate and reduce the residual deformation in the raw materials. The treated TA15 alloy wire was installed on the wire feeding mechanism of the electron beam fuse deposition equipment, and the treated TA1 pure titanium substrate was clamped on the motion system in the vacuum chamber of the equipment. When the vacuum degree of the vacuum chamber of the electron beam fuse deposition equipment reaches the use requirement (9.9 × 10 -3 The following processing parameters were set: acceleration voltage was 60 kV, focusing current was 1030 mA, wire feeding speed was V F The printing speed is 1.4m / min, T is 800mm / min, beam density I B The current is 25 mA. According to the one-way straight line path scanning mode, the printing program under the process parameters is edited in the automatic operation window of the electron beam fuse deposition equipment. The printing program is executed to complete the rapid preparation of the electron beam fuse deposition of the TA15 alloy. The gradient TA15 titanium alloy manufactured by the electron beam fuse additive manufacturing is obtained. The length is greater than 60 mm and the height is greater than 40 mm. The actual picture of the TA15 titanium alloy is as follows Figure 1 shown.
[0048] In this embodiment, if Figure 4 As shown in Figure 2, the upper, middle and lower regions (referred to as Top, Middle and Bottom) are dominated by the α phase with a close-packed hexagonal structure accompanied by a very small amount of the β phase with a body-centered cubic structure; the phase map also shows that the peak intensity of the α phase in different regions is slightly different, which means that the orientation of the α phase changes in the deposition height direction, from Figure 3From the microstructure shown, it can be seen that the microstructure of the gradient TA15 titanium alloy object is divided into the area close to the substrate, and the upper, middle and lower parts based on the distance from the TA1 substrate in the deposition direction. The fine basket structure is distributed in the area close to the substrate. As the height increases, the thickness of the α layer increases first and then decreases. The top area shows finer α layers, which is attributed to the coupling effect of thermal cycle and phase change cooling rate. Due to the strong cooling effect of the substrate, although the area close to the substrate experiences the most thermal cycles, it forms fine α layers. The faster cooling rate makes the α phase experience a shorter growth time. As the deposition height increases, the continuous heat input leads to the accumulation of a large amount of heat, which cannot be dissipated in time, thereby making the α layer coarser. However, as the height increases further, the number of thermal cycles also decreases, which shortens the growth time of the α layer phase at high temperature, thereby reducing the thickness of the α layer phase. In essence, the temperature and duration experienced by the α layer determine its thickness.
[0049] In this embodiment, Figure 6 Shows Figure 1 The tensile properties of the gradient TA15 titanium alloy formed by deposition in different areas of the upper, middle and lower parts (the loading direction is perpendicular to the deposition height direction). Figure 6 It can be seen that the tensile properties of the deposited TA15 titanium alloy in different areas are not very different, but the top area without a complete thermal history shows better comprehensive mechanical properties, with a yield strength of 915 MPa and an elongation of 12%, while the bottom area with a coarser α layer has lower strength and plasticity, which shows that the gradient mechanical properties of the gradient TA15 alloy depend on its gradient microstructure characteristics. It can be seen that the electron beam fuse additively manufactured TA15 alloy in this embodiment shows a gradient change in organization and performance along the deposition height, and is a typical gradient TA15 alloy.
[0050] In summary, the electron beam fuse additive manufacturing method can realize the preparation of gradient TA15 alloy. By adjusting the process window and selecting the optimal deposition process, a gradient TA15 alloy with good forming, dense structure, specific tissue orientation and excellent mechanical properties can be obtained. It plays a great role in shortening the processing flow and preparing TA15 alloy parts with complex configurations. It can also be extended to the near-net forming of other high-melting-point and high-activity alloys, and realize the rapid preparation of complex configurations with integrated structure and performance.
[0051] Furthermore, the composition of TA15 alloy wire is: Al 6.58wt.%, V 2.3wt.%, Zr 1.94%wt.%, Mo.1.42wt.%, Si≤0.05wt.%, Fe≤0.05wt.%, O≤0.1wt.%, N≤0.01wt.%, C≤0.01wt.%, H≤0.01wt.%, and the rest are Ti elements and unavoidable impurity elements; the composition of TA1 substrate is 99.9wt.% Ti element and other avoidable impurity elements.
[0052] Furthermore, in the above technical solution, the angle between the wire feeding nozzle for assembling the printing wire and the TA1 substrate is controlled to be about 40° to ensure the liquid bridge transition in the additive manufacturing process.
[0053] Furthermore, in the above technical solution, the length of the printing wire extending from the wire feeding nozzle to the center axis of the electron beam is 5-15 mm, so as to reserve a safety space to protect the wire feeding nozzle and ensure safe wire feeding.
[0054] Specific implementation method 2: See Figure 1-6 The present embodiment is described. The difference between the present embodiment and the specific embodiment 1 is the processing parameters. The processing parameters of the present embodiment are: the acceleration voltage is 60 kV, the focusing current is 1030 mA, the wire feeding speed is V F The printing speed is 1.4m / min, T is 800mm / min, beam density I B The current is 30 mA, and the rest of the processing techniques and steps are the same as those in the first embodiment. The actual gradient TA15 titanium alloy obtained in this embodiment is shown in FIG. Figure 2 shown.
[0055] Specific implementation method three: see Figure 1-6 The present embodiment is described. The difference between the present embodiment and the first embodiment is only in the processing parameters. The processing parameters of the present embodiment are: the acceleration voltage is 60 kV, the focusing current is 1030 mA, and the wire feeding speed is V F The printing speed is 1.2m / min, T is 800mm / min, beam density I B The current is 30 mA, and the rest of the processing techniques and steps are the same as those in the first embodiment. The actual image of the gradient TA15 titanium alloy obtained in this embodiment is shown in Figure 3.
[0056] The embodiments of the present invention disclosed above are only used to help illustrate the present invention. The embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. According to the content of this specification, many modifications and changes can be made. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well.
Claims
1. An electron beam fuse additive manufacturing method for gradient TA15 titanium alloy, characterized in that: It includes the following steps: Step 1: Pre-treat the printing filament and additive substrate; Step 2: Set up the printing program, build a 3D solid model based on the target TA15 titanium alloy, import the slices, set the scanning path, preheating parameters and printing process parameters; Step 3: Turn on the device and evacuate to 9.9×10 -3 Pa, TA15 alloy printing is performed according to the set printing parameters and procedures to complete all layers.
2. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 1, characterized in that: In step 1, the additive substrate is a TA1 substrate with a substrate size of 200 mm × 10 mm × 10 mm, and the printing filament is a TA15 alloy filament with a filament diameter of 1.6 mm.
3. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 2, characterized in that: The preprocessing in step 1 includes the following steps: S1: Soak the TA15 alloy wire in acetone for cleaning; S2: Place the TA15 alloy wire in a drying oven and dry it at a constant temperature of 60°C for 4 hours; S3: Use an angle grinder to grind the surface of the TA1 substrate until it is smooth; S4: Wipe the surface of the TA1 substrate with acetone and alcohol, and then soak and clean it with acetone; S5: Place the TA1 substrate in a drying oven and dry it at a constant temperature of 60° C. for 4 hours.
4. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 2, characterized in that: The composition of TA15 alloy wire is: Al 6.58wt.%, V 2.3wt.%, Zr 1.94%wt.%, Mo.1.42wt.%, Si≤0.05wt.%, Fe≤0.05wt.%, O≤0.1wt.%, N≤0.01wt.%, C≤0.01wt.%, H≤0.01wt.%.
5. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 2, characterized in that: The TA1 substrate contains 99.9wt.% Ti element.
6. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 2, characterized in that: The angle between the wire feed nozzle of the printing filament and the TA1 substrate is controlled at 40°.
7. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 2, characterized in that: The length from the wire feeding nozzle of the printing wire to the center axis of the electron beam is 5-15mm.
8. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 1, characterized in that: The preheating parameters in step 2 are: acceleration voltage of 60 kV, focusing current of 1030 mA, beam density of 25 mA, and preheating printing speed of 500 mm / min.
9. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 1, characterized in that: The printing process parameters in step 2 are: acceleration voltage of 60 kV, focusing current of 1030 mA, beam density of 25-30 mA, printing speed of 800 mm / min, wire feeding speed of 1-1.4 m / min, knob control speed coefficient of 80%, and interlayer cooling time of 5 s.
10. The electron beam fuse additive manufacturing method of a gradient TA15 titanium alloy according to claim 1, characterized in that: The scanning path in step 2 is a unidirectional linear motion path.
Citation Information
Patent Citations
3D printing processing method for TA15 titanium alloy aviation component
CN116748527A
titanium alloy, titanium alloy article and production thereof
NO962434D0